Autoria reflexiva coletiva : reconstrução do conhecimento químico escolar e autonomia emancipatória de professores de química - Mesquita, Joyce Melo (2023)
This research is developed by secundary school chemistry teachers, which it aims to understand the purpose of continuous training through a Collaborative Reflexive Authorship of a teaching program for first grade high school and its contribution for School Chemistry Knowledge rebuilding and for Emancipating Teachers Autonomy. It is developed by me with three secundary school chemistry teachers, it is a qualitative approach research, combining the critical-action research and narrative research methods in order to answer in which terms a proposal of continuous training starting from the Collaborative Reflexive Authorship of a chemistry teaching program for first grade high school contributes to school chemistry knowledge rebuilding and to emancipating secundary school chemistry teachers autonomy? The training proposal was inspired in the spiral phases of action research: i. problem´s definition (lack of teachers´ autonomy in order to make possible the chemistry teaching program authorship); ii. Planning and reflection (critical reflection about conception and practices of authors-teachers to enable the Collaborative Reflexive Authorship); iii. Action (Collaborative Reflexive Authorship of chemistry teaching program to high school first grade); iv. Evaluation and replanning (analysis and critics about the production process of authors-teachers and their contributions to teachers’ autonomy expansion and learning of School Chemistry knowledge, besides the possibilities of spiral training expansion to other spaces which are placed by authors-teachers). The audios-recordings transcriptions of the group´s meeting, getting together with the writing productions of Chemistry teaching program, they are part of the research corpus which were analyzed by the discursive text analyzes which enabled the emergence of three analytic categories, to get to know: (i) reproduction versus authorship epistemological struggles in the chemistry teachers training. (ii) Collaborative Reflexive Authorship: rebuilding of school chemistry teaching knowledge and (iii) Teachers autonomy expansion of authors-teachers: living the training models transition. The results´ analyzes enabled me to defend the thesis that in continuous training processes, the Collaborative Reflexive Authorship of Chemistry teaching programs by secundary education teachers, enhanced by critical reflection in/of own teaching and rebuilding of School Chemistry Knowledge, it provides the specialized teachers knowledge, it guides the critical thinking in teaching decisions that enables and increases the teachers’ autonomy expansion. The results express that Collaborative Reflexive Authorship helps out the enhanced in studies and researches about Schools Chemistry Knowledge, building own meanings to the schools, in a rebuilding process focused in the teachers practices, having in mind the importance of connecting the common sense to the scientific one, in order to enable the knowledge curriculum production which is commited with critical students training. The continuous training proposal that was lived by us, it raised the emergence of important training principles to the professional development of experienced teachers of the schools, it was guided by the following structuring elements: (i) the collaborative reflection about the action; (ii) the curriculum production with a critical approach and (iii) the specialized teachers partnership in virtual environments. At last, the School Chemistry Knowledge rebuilding in collaborative curriculum production enhances the extension of expansion teachers autonomy, in a way that enables an epistemological shift of individual reproductive practices to the collaborative reflective authorship.